Winning images showcase filter manufacturer. Issue 1 (January 2017) - Unknown
Abstract : Specialist filter manufacturer, Croft Filters, has been designing and manufacturing bespoke filter components for 30 years. For the last seven years, its marketing manager, Rob Watkins, has been photographing members of the Croft team at work and his award-winning images have gained national recognition.